Averrhoa Bilimbi Linn c Respiration Study in Passive Modified Atsmosphere Storage: - Kurniawan Yuniarto; Anang Lastriyanto; Cahyo Mustiko Okta Muvianto; Nurtiti Nurtiti (PERTETA, 2021)
Passive modified atmosphere storage (P-MAS) is a popular fresh fruits and vegetables storage method. The P-MAS creates naturally gas composition alteration due to aerobic respiration rate during storage which implies to maturity and shelf life. This research studied Averrhoa bilimbii Linn respiration behaviour by applying P-MAS at ambient temperature for 24 hours storage period. The gas composition was measured using typical zirconium and infrared gas sensor to determine oxygen and carbondioxide concentration. Heat and humidity were also logged by modifying SHT10 sensor. Acid titratic and weight loss represented the substrat consumption during respiration. The result investigated fastest respiration rate achieved at about RO2 28,60 ml [O2] kg-1 h-1 and (RCO2) sebesar 56,64 ml [CO2] kg-1 h-1 for an hour storage. The RQ was calculated above 1,0 for all period storage which indicated consumed organic acid material. Titratic acid reduced by 0,03 mg equivalent/100 g and average weigh loss was at about 0,04%. The Averrhoa bilimbi linn was categorized at sour-unripe during 24 hours storahe period and exponantially regression predicted sour-ripe level achieved after 37 hours.